Compartimentação geomorfológica do Gráben do Tacutu, Centro-Nordeste de Roraima - Nascimento, Silas de Oliveira (2016)
The Takutu Graben, located in the central-northeast of the state of Roraima, consists of an extensional segment, corresponding to an intracontinental rift deployed in the Mesozoic in a reactivated zone of the Central Guyana Belt, where the main structures are preferentially oriented NE-SW. The depth of the basin can reachs even thousand meters, filled by a sedimentary sequences pans from the Middle Jurassic to the Quaternary include in related to the pre-rift. The current level of geological know ledge of this basin is due to the interest in the exploitation of oil and gas. In this context, the aim of this work is to apply photointerpretative techniques of the remote sensing, in order to obtain morphostructural maps, understand the tectonic evolution and characterize the main geomorphologic compartments of the Takutu graben. The photointerpretative techniques applied followed the procedures of system a logical method with the introduction of in novations like GIS environment generation of thematic map the linear elements of drainage and relief photointerpreted. The morphostructural map generated showed two sets of morphostructures, one inside of the graben and the other in the it sedge regions. Both of them possess structural arrangements that reflect thetectono-stratigraphic evolution of this graben. Finally, using the methodology employed more refine disinformation were obtained, contributing to knowledge about the evolution of the Takutu graben morphostructural and its relationship to the tectonic processes and should assist in developing models for the exploration of prospective oil and gas.